Tradición y originalidad en la obra de Eneas el táctico: la génesis de la historiografía militar - Vela Tejada, José (Minerva: Revista de filología clásica, 1993)
The study about the work of Aeneas the Tactician in relation to the historical context and literary witnesses allows to enclose it inside the evolution towards a writing culture which begins from the last years of the Vth century B. C. In spite of the ancient military historiography has not been shaped as a literary genre in his work, we may infer, at least, Aeneas was the pioneer of a writing tradition which acquired a definitive status in the limits of the historical and literary context.